Effects of myocardial ischaemia on left ventricular untwist and filling pressure. Issue 9 (17th February 2011) - Lam, Willis; Leano, Rodel; Haluska, Brian; Marwick, Thomas H
Abstract : Objective: To link ischaemia, left ventricular (LV) untwisting and changes in filling pressure during dobutamine stress echocardiography (DSE). Design: Cross-sectional study at rest and at peak dobutamine stress. Setting: Academic medical centre. Patients: Patients who had undergone routine DSE between January and September 2009. Methods: Routine DSE was combined with measurement of transmitral pulsed-wave Doppler, myocardial tissue Doppler and speckle-tracking echocardiography at baseline and peak dose in 110 patients (51 women, 62±12 years). Untwisting rates (proto-diastolic and during isovolumic relaxation time (IVRT)) were measured by speckle tracking. Raised filling pressure was defined as E/e′>15. DSE studies were classified into normal, ischaemic or scar responses, independent of E/e′. Main outcomes: Echocardiographic outcomes. Results: Patients were categorised in three groups: group 1 (n=44), normal resting and peak E/e′; group 2 (n=33), normal resting E/e′ but raised peak E/e′; group 3 (n=33), abnormal resting E/e′. Risk factors and resting ejection fraction were similar in each group. Proto-diastolic untwisting rate was an independent predictor of raised filling pressure at peak stress (r 2 =0.3, p=0.03). An abnormal filling response during DSE was independently predicted by resting untwisting rate (UTR)-IVRT (p=0.003), and resting E/a (p=0.0001) (model pseudo-r 2 =0.76). Proto-diastolic UTR was lower in the ischaemic and scar groups at peak. Conclusion: Patients with abnormal filling pressure response have an impaired LV untwisting rate during isovolumic relaxation. This phenomenon supports the role of impaired LV suction as the mediator of the effect of myocardial ischaemia during DSE on filling pressure response to stress.